POLA KOMUNIKASI GURU DALAM PERKEMBANGAN BELAJAR SISWA DENGAN METODE PEMBELAJARAN DARING - Egi Famela; Agus Naryoso; Yanuar Luqman (Interaksi Online, 2023)
The pattern of communication is interpreted as a form of connection between two or more people in sending and receiving messages in the right way so that the intended message can be understood (Djamarah: 2004, p.1). What teachers experience during online activities in enhancing student learning development is that the majority of teachers feel confused at the start of online teaching and learning activities. This is because it happens suddenly, like it or not, it has to be done without prior preparation or training, be it teachers, students, or parents. Plus during the pandemic, many parents of students lost their jobs, so it was difficult for them to buy quotas so that their children could continue studying from home. Not only that, teachers also complain about not being able to create chemistry between teachers and students as it should be. It is more difficult for students to grasp the material presented online, this can be seen from the majority of assignments given to students, the average student doing is their parents. This study uses the theory of communication competence, theory of communication skills, theory of symbolic interaction, theory of conversational analysis.